Elastic Response of an Optimal Tensegrity-Type Metamaterial - De Tommasi, Domenico; Puglisi, Giuseppe; Trentadue, Francesco (Frontiers in Materials, 2019)
We analyze the optimization problem for metamaterials constituted by periodic patterns of tensegrity cells. Specifically we optimize compressed slabs constituted by tensegrity cells whose sections on the middle plane are equilateral triangles, squares or regular hexagons. Interestingly, we obtain a power law dependence of the density of the slab on the design applied stress, with invariant geometrical properties of the constituent cell. This result supports previous results regarding length scale invariance properties. Another very attracting property of the studied slabs is a very small tangential stiffness compared with its normal stiffness. This property is particularly interesting in the perspective of the design of innovative isolation devices with extreme properties.